Remdesivir Resistance in Transplant Recipients With Persistent Coronavirus Disease 2019. (26th September 2022) - Hogan, John I; Duerr, Ralf; Dimartino, Dacia; Marier, Christian; Hochman, Sarah E; Mehta, Sapna; Wang, Guiqing; Heguy, Adriana
Abstract: New mutations conferring resistance to SARS-CoV-2 therapeutics have important clinical implications. We describe the first cases of an independently acquired V792I RNA-dependent RNA polymerase mutation developing in renal transplant recipients after remdesivir exposure. Our work underscores the need for augmented efforts to identify concerning mutations and address their clinical implications.